CPCT image combination algorithm for 3D cephalometry - Burlakov , Pavlo (The Ukrainian Scientific Medical Youth Journal, 2024)
3D cefalometry as a method of diagnosis of orthodontic patients for treatment planning has many advantages over the classical adopted as the "gold standard" 2D, but its main disadvantage is the large retgenological load on the patient when conducting MSCT or CBCT of a large field of vision (FOV 25*25 cm). To develop an ALARA principle (As Low As Reasonably Achievable) diagnostic protocol and reduce the dose-area product (DAP) per patient during 3D orthodontic diagnostics (cephalometry) by combining CPCT images taken on a scanner with a smaller field of vision (FOV). Methods : CBCT images of the upper and lower jaw and temporo mandibular joints of the middle patients who sought dental assistance at the «Expir» clinic. Mimics Medical software (Materialise, Belgium) Based on our developed and patented method of cephalometric analysis DVB, it has been shown that it is possible to perform a cephalometry analysis and to plan orthodontic treatment on combined CBCT images and thus reduce the DAP for the patient to 1532 mGr*cm2. The digital approach to the improvement of diagnostic methods, developed in accordance with the ALARA principles, allows to improve the quality of orthodontic services and reduce the X-ray load on patients.